Molecular Docking Analysis of Used Drugs for the Treatment of Cancer - Demirbağ, Aliye Demet; Çelik, Sefa; AKYÜZ, SEVİM; Özel, Aysen (Süleyman Demirel Üniversitesi, 2021)
In this study, the lowest energy molecular structures were determined by conformational analysis of six drugs commonly used in cancer treatment, in order to use as initial data for docking simulations. Using the AutoDock Vina software, the interaction mechanisms of the 6 FDA approved drugs (Pemetrexed, Irinotecan, Tamoxifen, Gemcitabine, Topotecan and Temozolomide) with DNA were investigated. In addition, MM/PB(GB)SA calculations for the drug-DNA structures under investigation have been performed. The calculated binding affinities and binding free energies of interactions were showed the stability of the structures. It has been found that the active site where these molecules interact with DNA is the same and that their various interactions, primarily hydrogen bond, play an important role in this stability of the structures. Furthermore, the pharmacophoric features of the investigated molecules were determined.The aim of the work is to deeply investigate the binding properties of the title drugs with DNA.
Kanser Tedavisinde Kullanılan İlaçların Moleküler Kenetlenme Analizi
Keywords: Cancer; Drugs; Molecular Modeling; Conformational Analysis; Molecular Docking